A gamut of undiscovered electrophysiological effects produced by Tityus serrulatus toxin 1 on NaV-type isoforms. (August 2015) - Peigneur, Steve; Cologna, Camilla T.; Cremonez, Caroline M.; Mille, Bea G.; Pucca, Manuela B.; Cuypers, Eva; Arantes, Eliane C.; Tytgat, Jan
Abstract: In the last decades, Ts1 has not only been the subject of many studies, it has also been considered as a very useful tool to investigate NaV channels and to explore the exact role of NaV channels in channelopathies. Ts1 is believed to modulate the activation process of NaV upon interaction at the neurotoxin binding site 4. Our aim was to carry out an in depth functional characterization of Ts1 on a wide array of Nav channels, in order to investigate its mechanism of action and to verify if Ts1 can indeed be considered as a prototype site 4 selective toxin, valid for all the Nav isoforms we know currently. Ts1 has been subjected to an in-depth functional investigation on 9 NaV isoforms expressed in Xenopus laevis oocytes. Ts1 does not only interfere with the activation process but also modulates the inactivation in a bell-shaped voltage-dependent matter. Furthermore, Ts1 altered the ion selectivity through insect NaV . without influencing the tetrodotoxin selectivity of the channels. Finally, Ts1 was also found to inhibit the sodium current through the cardiac Nav 1.5 isoform. On the basis of the totally unexpected plethora of Nav modulations as induced by Ts1, we demonstrate that caution is required in interpretation the in vivo experiments when using Ts1. The electrophysiological characterization of Ts1 indeed shows that the general accepted contours of NaV binding sites are much more obscure than believed and that interpretation of NaV pharmacology upon toxin binding is more complex than believed thus far. Highlights: Ts1 induces a plethora of NaV modulations. Ts1 is capable of inducing an extreme modulation of insect Nav channels. The accepted contours of NaV binding sites are much more obscure than believed. Ts1 induces the inactivation process in a bell-shaped voltage-dependent manner. New insights in the mechanism through which toxins exerts their channel modulation.